Feminist Analysis of Human Rights Law - Shazia Qureshi (Journal of Political Studies, 2012)
The rhetoric of human rights declares the idea to be universal (Universal Declaration of Human Rights, 1948), this claim inevitably poses a serious challenge when one tries to theorize human rights. In response to human right law’s selfproclaimed Universality and Neutrality, two major critiques have been developed which deny the truth of this assumption, namely Feminist and Cultural relativist. This article looks at the universality claim of human rights law from the feminist perspective, according to which, the human rights discourse is an extension of a gendered international legal system that fails to take into consideration the voices of women (Gottschalk, n.d.: 1). The article also explores the stance of cultural relativists on human rights law and shed light on the extent to which it is detrimental to feminist approaches.